2005
DOI: 10.1007/11550822_106
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection of Alzheimer’s Disease by Blind Source Separation, Time Frequency Representation, and Bump Modeling of EEG Signals

Abstract: Abstract. The early detection Alzheimer's disease (AD) is an important challenge. In this paper, we propose a novel method for early detection of AD using electroencephalographic (EEG) recordings: first a blind source separation algorithm is applied to extract the most significant spatio-temporal components; these components are subsequently wavelet transformed; the resulting timefrequency representation is approximated by sparse "bump modeling"; finally, reliable and discriminant features are selected by orth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 19 publications
(35 reference statements)
3
29
1
3
Order By: Relevance
“…Previous research by other authors had shown the utility of the BSS and component selection preprocessing when spectral and time-scale features were computed from EEGs of MCI patients who later proceeded to AD [12,22]. These EEG signals were characterised with the relative powers in six frequency bands [12].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous research by other authors had shown the utility of the BSS and component selection preprocessing when spectral and time-scale features were computed from EEGs of MCI patients who later proceeded to AD [12,22]. These EEG signals were characterised with the relative powers in six frequency bands [12].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a later study used a "bump modelling" of the partially reconstructed EEG wavelet time-frequency transform and a neural network classifier to further improve the subject classification [22]. In contrast to these studies, our classification method allowed us to assess the improvement in each variable (MF, SpecEn, LZC or SampEn) separately.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations